(untitled) (Research, Society and Development, 2021)
Objective: To analyze scientific evidence on the clinical profile, prevalence and mortality of adult hospitalized patients with chronic liver disease (CLD) infected with SARS-COV-2. Methodology: This is a bibliographic review in the integrative literature review method, carried out in February 2021, in the databases MEDLINE / PubMed, EMBASE and LILACS, using the descriptors / MESH: "COVID-19" AND "chronic liver disease ", combined with the Boolean operator "AND”. Inclusion criteria were: original articles available in full, complete, published between 2019 and January 2021, in Portuguese, English and/or Spanish, and a suitable theme. The exclusion criteria were: incomplete, duplicate articles, unrelated to the topic, in pre-proof, theses, dissertations, monographs and manuals. Results: Seven articles were included. 1693 adult hospitalized patients infected with SARS-COV-2 were analyzed and the frequency was varied between 0.79% and 50%, compared to the hospitalized population infected with COVID-19 with and without CLD. The clinical profile of patients with CLD and COVID-19 was predominantly male, mean age: 55 years, non-alcoholic fatty liver disease as a previous CLD and hypertension as the main comorbidity. The most reported symptoms were cough (80.8%), presence of infection(73.1%), sputum(26.9%), dyspnea(25%), myalgia or fatigue(13.5%). The main laboratory and imaging changes included elevation in liver enzymes, lymphopenia, diffuse opacities and ground-glass. Mortality was more significant in immunosuppressed CLD and COVID-19 patients, ranging from 1.78% to 8.1%. Conclusion: The data propose a trend in clinical profile, prevalence and mortality, but there is a need for further cohort studies or randomized clinical trials with larger samples to confirm hypotheses.